Predicting the potential implications of perch (Perca fluviatilis) introductions to a biodiversity-rich lake using stable isotope analysis - Tarkan, Ali Serhan; Haubrock, Phillip J; Aksu, Sadi; Mol, Oğuzcan; Balzani, Paride; Emiroğlu, Özgür; Köse, Esengül; Kurtul, Irmak; Başkurt, Sercan; Çınar, Emre; Oztopcu-Vatan, Pinar (Scientific reports, 2023)
Biological invasions, particularly of fish species, significantly threaten aquatic ecosystems. Among these invaders, the introduction of the European perch (Perca fluviatilis) can have particularly detrimental effects on native communities, affecting both ecosystem functioning and human well-being. In this study, carbon and nitrogen stable isotope analysis was employed, using perch originating from five different ecosystems, to model the effects of their hypothetical introduction into İznik Lake, an economically and ecologically important, biodiversity-rich lake in northern Turkey, to ultimately assess their potential predation impact and competition with native predators. The results revealed that if perch were introduced to the community, they would - considering gape size limitations - primarily prey upon Vimba vimba and Rutilus rutilus, indicating a significant feeding pressure on these species. Furthermore, the study identified a potential overlap and competition for resources between commonly mesopredator perch and the European catfish Silurus glanis, the current top predator in the ecosystem. Both species would occupy top predatory positions, emphasizing the potential disruption of predator-prey dynamics. Our findings underscore the potential ecological repercussions of perch invasions. The selective predation on V. vimba and R. rutilus, with the latter being consumed to a lesser extent by perch, could lead to cascading effects throughout the food web, altering the community structure, and ecosystem dynamics. Additionally, the competition between perch and S. glanis raises concerns about effects on the stability and functioning of the fish community. These results highlight the need for proactive management strategies to mitigate the risk of perch introductions. Strict regulations on the movement and introduction of invasive species, along with comprehensive monitoring, are crucial for preserving native communities and maintaining the ecological integrity of freshwater ecosystems. Our study demonstrates the potential predation impact of perch on vulnerable fish species and the competition with the established apex predator, emphasizing the importance of considering the ecological consequences of perch invasions and informing management decisions to ensure the conservation and sustainability of aquatic ecosystems.
Keywords: predátorské chování; Nitrogen Isotopes; Ecosystem; Perches; Lakes; izotopy dusíku; jezera; Cyprinidae; Catfishes; Predatory Behavior; zavlečené druhy; Animals; lidé; okounovití; Humans; zvířata; Introduced Species; ekosystém; sumci